Targeted Isolation of Coumarins From Sideritis Species Based on Antiviral Screening and Untargeted Metabolomics - Tomou, Ekaterina Michaela; Engler, Olivier; Chrysargyris, Antonios; Tzortzakis, Nikos G.; Skaltsa, Helen; Urmann, Corinna (My University, 2025)
The SARS-CoV-2 pandemic has revealed a deficiency in antiviral agents. Plants, traditionally used for respiratory infections, are valuable sources of antiviral compounds. Such a plant is the Sideritis L. taxa (mountain tea), traditionally used against cold and cough.
Keywords: GC–MS; Lamiaceae; antiviral effect; metabolite profile; mountain tea